Analysis of squirrel-cage induction generator start-up supported by reactive power compensator. Issue 2 (16th November 2019) - Górski, Dominik Andrzej
Abstract : Purpose: The power electronic converter is used for the satisfaction of reactive power demand of induction generator, when grid-tied. This paper aims to present an application of STATCOM to reduce inrush transient caused by the connection of a squirrel-cage induction generator (SCIG) to the grid. Design/methodology/approach: The power generation system consists of an uncontrolled prime mover, a SCIG and a power electronic converter connected to the grid. The three-phase Neutral Point Clamped (NPC) converter works as a STATCOM to satisfy a reactive power demand of the generator. A control scheme of STATCOM uses the x-y reference frame rotating synchronously with grid voltage vector and the p-q instantaneous power theory to calculate q component of grid power. Findings: It is shown that the parallel converter, which works as a reactive power compensator allows decreasing transients during a grid connection of the induction generator. Research limitations/implications: Transients during a grid connection of the induction generator are only partially decreased. Practical implications: It is needed to compensate for the reactive power of a SCIG. The NPC converter works as a STATCOM. The converter partially reduces grid transients during generator connection. The laboratory tests are demonstrated by connection 7.5 kW induction generator to 8 kVA transformer. Originality/value: The paper presents the mitigation of grid transients during connection of induction generator with the power electronic converter working as reactive power compensator.